2014
DOI: 10.1007/s10103-014-1682-5
|View full text |Cite
|
Sign up to set email alerts
|

Porcelain laminate veneer conditioning for orthodontic bonding: SEM-EDX analysis

Abstract: The purpose of this in vitro study was to evaluate and compare the effects of different surface treatments and laser irradiation on the bond strength of brackets bonded to porcelain laminate veneer. Porcelain laminate veneer specimens were embedded in the centers of acrylic resin blocks. Thirty-nine teeth were used for shear bond strength testing and the remaining three (one tooth for each group) were used for evaluation of the debonded bracket interface. Specimens were randomly divided into three groups, each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…It is preferable to use low pressures (1-2 bar) using powders with particles smaller than 50 μ m when conditioning ceramic surfaces [ 54 ]. Interestingly, some studies from the 1990s up to more recent years have indicated that AA with 50 μ m aluminium oxide particles produces insufficient bond strength of ceramic to composite [ 56 , 81 , 82 ]. This, again, is likely because ceramics react differently to conditioning techniques [ 77 , 83 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is preferable to use low pressures (1-2 bar) using powders with particles smaller than 50 μ m when conditioning ceramic surfaces [ 54 ]. Interestingly, some studies from the 1990s up to more recent years have indicated that AA with 50 μ m aluminium oxide particles produces insufficient bond strength of ceramic to composite [ 56 , 81 , 82 ]. This, again, is likely because ceramics react differently to conditioning techniques [ 77 , 83 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Successful bonding of metal brackets to porcelain surfaces and their durability are influenced by several factors, such as preparation of porcelain surfaces, quality of bonding agents, photopolymerization process, and fatigue of bonding agents simulated by means of thermocycling (3)(4)(5). The preparation of the ceramic surface is an important step.…”
Section: Discussionmentioning
confidence: 99%
“…Different methods have been used to treat porcelain surfaces before bracket bonding so as to increase shear strength, thereby improving clinical bonding efficiency (4,5). According to the literature, application of hydrofluoric acid and silane prior to bracket bonding is the best alternative for preparation of ceramic surfaces (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Feldspathic ceramic is most commonly included in studies, as it is most often used in prosthodontics [15][16][17][18][19][20][21][22][23]. Only one research, published by Ahrari in 2013 [15], focuses on fractional CO 2 laser use by testing different intensities of 10 W, 15 W, 20 W and comparing them to hydrofluoric acid.…”
Section: The Effect Of Laser On Feldspathic Ceramicmentioning
confidence: 99%